ลักษณะการใช้ภาษาในการเขียนเรื่องเล่าของเด็กที่มีความบกพร่องทางการเรียนรู้ - ไชยสุข ปิยะภรณ์ นาคอาทิตย์; โปธิบาล พุทธชาติ (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: This study aimed to analyze characteristics of language usage and thinking patterns of children with learning disabilities through narrative writing, and to compare pre-test and post-test writing proficiency. METHODS: The study used a set of Nanci Bell’s drawings as a testing tool for narrative writing practices for four weeks. Pre-test and post-test were adopted for change evaluation. RESULTS: When comparing writing from the pre-test and post-test, there was an increase in quantity in terms of words, sentence writing, and cohesive devices. Nevertheless, the volunteer still had difficulties in choosing appropriate words to fit the narrative, arranging words in proper order, providing all necessary words, completing sentences, and expressing narrative unity. CONCLUSIONS: All of these reflected the scattered thinking system of the volunteer and language impairment from word to text. After providing narrative writing practice for four weeks, the volunteer developed better than pre-test, but not enough to organize his thinking and language perfectly.